Cash Transfers Increase Trust in Local Government - Evans, David K. (World Bank, Washington, DC, 2018)
How does a locally-managed conditional cash transfer program impact trust in government? On the one hand, delivering monetary benefits and increasing interactions with government officials (elected and appointed) may increase trust. On the other hand, imposing paternalistic conditions, leading some to experience feelings of social stigma or guilt, and potentially permitting capture by local elites could reduce trust. This paper answers this question by exploiting the randomized introduction of a locally-managed transfer program in Tanzania in 2010, which included popular election of community management committees to run the program. The analysis reveals that cash transfers can significantly increase trust in leaders. This effect is driven by large increases in trust in elected leaders as opposed to appointed bureaucrats. Perceptions of government responsiveness to citizens' concerns and honesty of leaders also rise; these improvements are largest where there are more village meetings at baseline. One of the central roles of village meetings is to receive and share information with village residents. One indicator that governance may have improved is that records from school and health committees are more readily available in treatment villages. Notably, while the stated willingness of citizens to participate in community development projects rises, actual participation in projects and the likelihood of voting does not. Concerns that local management of a cash transfer program will destroy trust in government or reduce the quality of governance appear unfounded—especially in high-information contexts.